2020
DOI: 10.31234/osf.io/b5tcp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Self-Awareness on the Identification of Goal-Related Obstacles

Abstract: When individuals strive towards personal goals, they may encounter obstacles that could compromise their goal progress and pose a challenge to self-regulation. Coping with obstacles first requires those obstacles to be identified. The purpose of the present studies was to apply an inter-individual approach to this important, but insufficiently studied self-regulatory aspect of goal striving. We therefore examined the role of self-awareness, that is, paying attention to one's own feelings, thoughts, and behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…This is also considered an essential skill in the field of teaching, as self-reflection enhances the ability of an educator to be more aware of the progress of his/her students, as well as, be mindful of the adjustments needed to be made (Herbert-Smith, 2023). Moreover, studies have found that self-reflection is important for identifying obstacles to goal completion and that general self-reflection seemed to predict life satisfaction more broadly; the implication being that paying attention to aspects of the self will promote the process of comparing ideal states with actual states, assisting in goal-setting, and enabling successful completion of personal goals (Kreibich et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This is also considered an essential skill in the field of teaching, as self-reflection enhances the ability of an educator to be more aware of the progress of his/her students, as well as, be mindful of the adjustments needed to be made (Herbert-Smith, 2023). Moreover, studies have found that self-reflection is important for identifying obstacles to goal completion and that general self-reflection seemed to predict life satisfaction more broadly; the implication being that paying attention to aspects of the self will promote the process of comparing ideal states with actual states, assisting in goal-setting, and enabling successful completion of personal goals (Kreibich et al 2020).…”
Section: Introductionmentioning
confidence: 99%